2020
DOI: 10.1111/ppc.12569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activity groups, in which art activities are used, on resilience and related factors in families with disabled children

Abstract: Purpose: This study aims to examine the effects of activity groups using art activities on resilience and related factors in mothers with disabled children. Design and Methods: This randomized controlled experimental design study was conducted with 33 mothers (18 in the control and 15 in the intervention group). Findings: A statistically significant difference was found between the intervention group's pretest and posttest mean scores on the Resilience Scale for Adults, the Satisfaction with Life Scale, Zarit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…As a result, it was determined that the art activities used increased psychological well-being and life satisfaction in the families of disabled children and that they decreased the mothers' perceived caregiving. In the study, along with other activities in addition to art activities, the comfort level of the individual was aimed to be increased; the comfort created at emotional, physical and environmental levels also affected the life satisfaction of the individual (Culhacik et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, it was determined that the art activities used increased psychological well-being and life satisfaction in the families of disabled children and that they decreased the mothers' perceived caregiving. In the study, along with other activities in addition to art activities, the comfort level of the individual was aimed to be increased; the comfort created at emotional, physical and environmental levels also affected the life satisfaction of the individual (Culhacik et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study stated that colouring exercises of adult individuals as a self‐initiated, easy and enjoyable activity could provide support to them in their daily lives in order to fix negative mood and decrease worry and anxiety symptoms (Cross & Brown, 2019). Culhacik et al (2021) examined the effect of the art activity performed by groups of families with disabled children on their tenacity and related factors. In the said study, an activity consisting of music, painting, collage, dance/movement and imagination within the scope of a semi‐structured plan was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the study of Keniş-Coşkun showed that stressful life events, such as having a child with a disability, result in a lower level of resilience [21]. Mothers of disabled children experience reduced resilience and their general health and quality of life are negatively affected; therefore, they perceive a heavy caregiving burden [22]. It seems that the reason for the lack of difference between the resilience of mothers with disabled children and typically developed ones in Fasa lies in the similarity of individual characteristics, the cultural ground dominating this city including people's patience and tolerance, especially the lady fellow-citizens in dealing with the problems, adaptation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of disabled children experience reduced resilience and their general health and quality of life are negatively affected; therefore, they perceive a heavy caregiving burden. These mothers need emotional sharing and psychological and psychosocial support to cope with their children's disability and to maintain their mental and physical health [22]. An increase in resilience reduces the level of stress and mental pressure [23], promotes mental health [24], increases indicators of wellbeing [25], and improves the quality of life [26][27][28].…”
Section: Introductionmentioning
confidence: 99%